2022
DOI: 10.3390/pathogens11070759
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Detection and Prevalence Factors Associated with Common Respiratory Pathogens in Equids with Acute Onset of Fever and/or Respiratory Signs (2008–2021)

Abstract: A voluntary biosurveillance program was established in 2008 in order to determine the shedding frequency and prevalence factors for common respiratory pathogens associated with acute onset of fever and/or respiratory signs in equids from the USA. Over a period of 13 years, a total of 10,296 equids were enrolled in the program and nasal secretions were analyzed for the qPCR detection of equine influenza virus (EIV), equine herpesvirus-1 (EHV-1), EHV-4, equine rhinitis A and B virus (ERVs), and Streptococcus equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Many investigations showed that comparing with neuropathogenic strains (G2254), non-neuropathogenic strains (A2254) were the predominant genotype affecting primarily horses with respiratory disease [14,18]. Recently, four studies in Europe and the USA revealed a new EHV-1 DNA polymerase (ORF30) genotype C2254/H752 which was then associated with respiratory signs outbreak [9,12,13,15]. Whereas, in this study, neuropathogenic strains were detected in samples collected of horses with respiratory problem.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Many investigations showed that comparing with neuropathogenic strains (G2254), non-neuropathogenic strains (A2254) were the predominant genotype affecting primarily horses with respiratory disease [14,18]. Recently, four studies in Europe and the USA revealed a new EHV-1 DNA polymerase (ORF30) genotype C2254/H752 which was then associated with respiratory signs outbreak [9,12,13,15]. Whereas, in this study, neuropathogenic strains were detected in samples collected of horses with respiratory problem.…”
Section: Discussionmentioning
confidence: 56%
“…Several previous studies had shown that major viral respiratory pathogens considered were: equine in uenza virus (EIV), EHV-1, EHV-4, equine rhinitis viruses A (ERAV) and B (ERBV), and equine arteritis virus (EAV) [11][12][13]. One previously published report had been showed that H3N8 equine in uenza virus was pathogen for respiratory disease of China horse population [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, Florida Clade 1 is endemic in the United States, and the reports associated with Clade 2 belong to imported horses [ 82 ]. A prevalence of 9.3% was reported in horses with acute respiratory clinical signs in a study conducted from 2010 to 2013 [ 50 ], and recently, a rt-qPCR frequency of 6,8% was reported in a voluntary sampling of 10,296 equids with acute onset of fever and/or respiratory signs for rostral nasal secretions in the country between 2008 and 2021 [ 83 ]. Phylogenetic analyses of EIV H3N8 strains from 2012 to 2017 based on the HA gene have shown that H3N8 strains from the US underwent antigenic drift and fixed multiple substitutions accumulated in the HA gene [ 84 ] and that the H3N8 FC1 North American lineage was the major source of globally dominant EIV variants and spread to other global regions [ 85 ].…”
Section: Studies On Eiv Occurrence and Reported Outbreaksmentioning
confidence: 99%